Laser bleaching of tattoos: a new approach. (January 2021) - Shubnyy, A.G.; Zhigarkov, V.S.; Yusupov, V.I.; Sviridov, A.P.
Abstract: The dynamics of the formation and relaxation of microbubbles in a polyacrylamide phantom of tattooed skin under the action of a series of laser pulses with 15-ns duration is studied. It is shown that the growth of microbubbles occurs within a few milliseconds, and their lifetime varies from several seconds to several hours, depending on the water content in the phantom and the fluence (energy density) of laser radiation. It is found that the multipulse laser exposure regime, in comparison with the single-pulse regime, reduces the laser radiation fluence and significantly increases the degree of phantom bleaching. A region of parameters (number of pulses, fluence), in which a high concentration of undesirable (blocking laser radiation) long-lived bubbles does not form, while the bleaching effect reaches its maximum, is found. A mechanism for effective tattoo removal, based on selective thermolysis under conditions of a decrease in the thermal conductivity of the medium in the immediate vicinity of pigmented particles due to the formation of microbubbles, is proposed.